Liminal Performance in Hali Meiðhad - Lazikani, Ayoush Sarmada (Journal of medieval religious cultures, 2016)
As an epistle for virgins, the thirteenth-century text Hali Meiðhad facilitates the reader's embodied simulation of the suffering of an anguished, nonvirginal woman. The reader thus inhabits an uncomfortably liminal space between spectatorship and performance. This essay will focus on anchoritic readership of this epistle, a critical decision lent support by the text's linguistic and codicological associations. It will examine an anchoress's embodied simulation of pain in reading Hali Meiðhad, after interrogating her liminal position as both performer and spectator.